PERAN KEPOLISIAN DALAM PENANGGULANGAN BERITA HOAX DI MEDIA SOSIAL DI PROVINSI KALIMANTAN TENGAH - Rizki Setyobowo Sangalang (MORALITY: Jurnal Ilmu Hukum, 2020)
In the era of the industrial revolution 4.0 the use of social media in the community has become a daily habit of society, with the aim to increase economic needs by promoting products or services, sharing news, sharing lifestyles by sharing photos or writing / daily notes . It cannot be denied, social media provides a change in people's lives, there are no time and space limits for social activities. With all the facilities provided by social media, the news that cannot be accounted for is true / the hoax / hoax that is publicly aware. Not a few people who believe in the news hoaks. Hoaks news contains a lot of hate speech, provocation, slander and is very dangerous if circulated among the people because it can cause noise, suspicion, hostility, and even cause both moral and material harm. If you continue to let the news hoaks can damage the joints of national and state life. The police who have the duty as law enforcement, protector, protector, and guiding the community for the maintenance of security have an important role to cope with the many hoaks that are circulating in the community.